2022
DOI: 10.1212/wnl.0000000000200550
|View full text |Cite
|
Sign up to set email alerts
|

Teaching NeuroImage: Intradural ALK-Positive Histiocytosis With Involvement of Nerve Roots and Spinal Dura

Abstract: A 3-year-old boy presented with progressive lower extremity weakness and difficulty walking for 2 months. Neurologic examination found the muscle strength of his left lower limb was grade 3 and tendon reflex was weakened. MRI demonstrated an intradural extramedullary mass between T10-11 with multiple and diffuse enhancement of thickened nerve roots and spinal dura (Figure). Juvenile xanthogranuloma was suspected as positive staining for CD68 and negative for S100 and CD1a, while immunoreactivity for ALK did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A review of the literature revealed 17 previously published cases of ALK-H localized in the CNS, as summarized in Table 1. 6,[8][9][10][11][12] The age of patients ranged from 0 to 20 years old, and the median age was 7 years old. Six patients (35.3%) were male, and 11 (64.7%) were female.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed 17 previously published cases of ALK-H localized in the CNS, as summarized in Table 1. 6,[8][9][10][11][12] The age of patients ranged from 0 to 20 years old, and the median age was 7 years old. Six patients (35.3%) were male, and 11 (64.7%) were female.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, more than 60 cases of ALK-positive histiocytosis have been reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (see detailed information in Additional file 2: Table S3-5). In 2018, Chang et al classified ALK-positive histiocytosis into two types, systemic and localized, based on clinical manifestations [2].…”
Section: Discussionmentioning
confidence: 99%